B3 NC Symp 2018 - Stability Testing of Nitrocellulose - Ramin et al.pdf - Gill, Philip (Cranfield University, 2023)
Stability Testing of Nitrocellulose Michael Ramin, Beat Vogelsanger, Marc Müller, Beate Pausc Rheinmetal, Nitrochemie
Keywords: 'nitrocellulose'